Study and Development of Graphical Authentication System for Secure File Transmission - L.P.Ramyasri, P.; Malathi, D.; D. Dorathi Jayaseeli, J.; Senthilkumar, K. (International Journal of Engineering and Technology, 2018)
The text-based password has been the most common practice from ancient days till present. Text based pass-words are also known for various threats, and it is prone to attacks like guessing attacks, dictionary attacks, social engineering attacks, brute force attacks, etc. The next immediate concept following the text based password is the graphical password schemes to improve password security and usability. In present days graphical passwords are being implemented more commonly. This approach is different from the traditional alpha numeric as it deals with images. In this paper a survey study is done to analyse various techniques used for authentication and also some of the methods for graphical authentication techniques like Pass Matrix, Cued Clicked points(CPP), CAPTCHA, Image distortion with text association, Doodle scheme, Standard recognition-based scheme, Stegno pin authentication method. Based on the existing methods, the future research can be done in order to improve security for graphical authentication.Â Â